Leadership wisdom - Sharma, Robin (Ahmedabad : Jaico Publishing House, 2019)
This work reveals a step-by-step system that aims to restore trust, commitment and spirit within your organization while transforming the way you think, feel and live in the process. It distils its wisdom for both professional and personal leadership into eight practical lessons.
Keywords: Leadership